PENGARUH PRODUK BATIK DAN PRODUK IMPOR TERHADAP MOTIVASI BELANJA KONSUMEN WANITA DI PUSAT GROSIR SOLO - Indria, Desi Putri; Maryam, Hj. Siti (Surakarta Management Journal, 2019)
The aim in this paper are to: 1) Determine the influence of batik products and imported products simultaneously to shopping motivation of woman consumers in Pusat Grosir Solo. 2) Determine the influence of batik products and imported products partially to shopping motivation of woman consumers in Pusat Grosir Solo.Type a this research of causality descriptive. The research location in Pusat Grosir Solo. The population of this research were woman consumers who shop in Pusat Grosir Solo. The samples studied 100 respondents. Methods of data analysis used in this research were: 1) Instruments Test. 2) Classical Assumption Test. 3) Hypothesis Test. From the results of data analysis can be summarized as follows: 1) Batik products and imported products simultaneously affect to shopping motivation of woman consumers in Pusat Grosir Solo. 2) Batik products and imported products partially positive significant effect to shopping motivation of woman consumers in Pusat Grosir Solo. Multiple regression analysis was obtained coefficient of determination or Adjusted R Square of 43.7% that number have enough good quality research that studied independent variables have an effect on the dependent variable. While the balance of 56.3% is explained by other factors not participate observed.